On solving inverse kinematics of redundant robotic manipulators by using coordinate and velocity projection methods - Hoàng, Nguyễn Quang; Thảo, Thái Phương (Journal of Computer Science and Cybernetics, 2012)
A method for solving inverse kinematics of redundant robot is introduced in this paper. Firstly, inverse kinematics of redundant robotic manipulators is represented in two levels: velocity level and acceleration level. Solutions of these problems are given by pseudo inverse of the Jacobian matrix under consideration of null space in order to avoid joint limitations. Secondly, the values of joint variables are found by the integration which is revised by coordinate and velocity projection methods. By using this method the joint variables and joint velocities are adjusted such that they are forced onto manifolds defined by position constraints and velocity constraints. Therefore, the accuracy of solutions is significant improved. Some results of numerical simulations are illustrated for this method.